EFEKTIVITAS PEMBELAJARAN MATEMATIKA MATERI MATRIKS BERBASIS OUTDOOR LEARNINGPROCESS DAN OBSERVASI LANGSUNG - Nanda Dwi Mardiyanto (Universitas PGRI Adi Buana Surabaya, 2015)
The researcher is motivated by the fact the main problem in mathematics learning in school today is the low absorption ability of students as evidenced by the average student learning outcomes that regard. The reason that learning methods shown by the teacher dominated more teachers, so students tend to be passive and not given access to evolve independently. This illustrates that the process of learning that takes place is not optimal.This study aims to determine the activities of students and teachers, completeness student learning outcomes, and student responses, the learning of mathematics-based matrix material outdoor learning process and direct observation at SMA Kartika Wijaya Surabaya.The method used is the study is a One-Shot Case Study. This research was conducted in class XI student Mia with a total of 35 students. From the research that has been conducted Based on the analysis of student activity data showed a total average score of 3.12 classified as active student, teacher activity obtained average score of